Exploring the ecological and social benefits of the Khayelitsha Wetlands Park - Mathenjwa, Fezile (Department of Environmental and Geographical Science, 2018)
In a world confronted by rapid urbanization linked with dramatic population growth rates, there is a general consensus that quality urban green spaces are important components of urban landscapes. Urban green spaces are defined as open spaces in urban areas primarily covered with vegetation, which are available to users within the community. They have the ability to shape the image of cities and provide various important socioecological benefits, which can contribute to improving the quality of life within these urban communities. In Cape Town, the provision of readily accessible quality urban green spaces is often overridden by other conflicting demands, such as biodiversity conservation and infrastructure development demands. The literature suggests that Cape Town has ample available green spaces. However, the accessibility of this green space is linked to issues of poor management and maintenance, and as a result poor urban spaces are often associated with criminal activities, and are therefore unavailable to benefit urban communities. This is particularly evident in areas which have a low socioeconomic status. This study explores the ecosystem services offered by the Khayelitsha Wetlands Park in the Khayelitsha Township on the Cape Flats. A variety of methods were used to establish the condition of the Wetlands Park and assess the impacts of various uses (e.g. recreation, agriculture etc.) on the vegetation structure and water quality. Qualitative semi-structured interviews were also conducted to assess the local community's uses and perceptions of this green space. A Complex Adaptive Landscape (CAL) approach was adopted to derive the positive and negative social-ecological impacts of the Khayelitsha Wetlands Park. The vegetation structure assessment results showed a dominance of emergent and invasive vegetation, such as Typha capensis and Acacia cyclops, and indicates a high level of degradation and a lack of indigenous vegetation species. The water quality analysis reveals high concentrations of physiochemical and microbial pollutants, where a majority exceeded the Targeted Water Quality Ranges (TWQR) recommended by the Department of Water Affairs for livestock watering, irrigation and human use. Findings from the semi-structured interviews, revealed that a majority of users v visit the Park for multiple activities offered by the Park. These include relaxation, creating and maintaining social relations, sports and recreation and agricultural use. The CAL framework revealed negative and positive feedback mechanisms at play in this urban green space. The negative feedback effects are illustrated and confirmed by poor water quality and a predominantly alien infested vegetation structure. The poor ecological condition of the Wetland is linked to a number of anthropogenic influences, including the discharge of treated waste and untreated waste from both agricultural and urban waste sources, indicating the complexity of managing the Khayelitsha Wetlands Park. Since a number of users and management institutions are connected to the Khayelitsha Wetlands Park, their involvement in the management thereof is crucial for effectively solving the issues identified.